RNA Demethylase FTO Mediated RNA m6A Modification Is Involved in Maintaining Maternal-Fetal Interface in Spontaneous Abortion - Qiu, Weiyu; Zhou, Yuexi; Wu, Haiwang; Lv, Xiaoli; Yang, Lilin; Ren, Zhenxing; Tian, He; Yu, Qingying; Li, Jing; Lin, Weixian; Zhao, Ling; Luo, Songping; et al. (Frontiers in Cell and Developmental Biology, 2021)
The N6-methyladenosine (m6A) RNA modification regulates the expression of genes associated with various biological and pathological processes, including spontaneous abortion (SA). The aim of this study was to determine the role of the m6A demethylase fat mass and obesity (FTO)- associated protein in SA. The FTO,IGF2BP1 and IGF2BP2 mRNA levels were significantly lower in the chorionic villi obtained from spontaneously aborted pregnancies compared to that of normal pregnancies, while the expression levels of METTL3 and WTAP were significantly elevated. However, ALKBH5, YTHDF2, and IGF2BP3 were elevated with no statistical significance between groups. In addition, MDA was elevated and SOD levels were decreased in the villi tissues of the SA group compared to the normal group, which was indicative of placental oxidative stress in the former. Furthermore, the expression of FTO and HLA-G were significantly decreased in the trophoblasts of the SA patients compared to that of normal pregnant women, while that of m6A was markedly higher in the former. In addition, the HLA-G and VEGFR mRNA levels were downregulated in the SA versus the control group, and that of MMP2, MMP7, MMP9 and VEGFA were upregulated. Finally, The RIP assay showed significantly decreased levels of FTO-bound HLA-G, VEGFR and MMP9 RNA in SA patients (P < 0.05), which corresponded to an increase in transcripts enriched with the m6A antibody (P < 0.05). However, compared with normal pregnant women, the levels of HLA-G, VEGFA, VEGFR, and MMP2 mRNA bound by YTHDF2 were significantly decreased in SA patients. Compared to the normal pregnant women, both FTO- and m6A-bound MMP7 were significantly increased in SA patients (P < 0.05), but YTHDF2 almost unbound to MMP7 mRNA. In summary, the downregulation of FTO in the chorionic villi disrupts immune tolerance and angiogenesis at the maternal-fetal interface, resulting in aberrant methylation and oxidative stress that eventually leads to SA.